Sage Insights Into the Phylogeny of Salvia: Dealing With Sources of Discordance Within and Across Genomes - Rose, Jeffrey P.; Kriebel, Ricardo; Kahan, Larissa; DiNicola, Alexa; González-Gallegos, Jesús G.; Celep, Ferhat; Lemmon, Emily M.; Lemmon, Alan R.; Sytsma, Kenneth J.; Drew, Bryan T. (Frontiers in Plant Science, 2021)
Next-Generation Sequencing technologies have facilitated new phylogenomic approaches to help clarify previously intractable relationships while simultaneously highlighting the pervasive nature of incongruence within and among genomes that can complicate definitive taxonomic conclusions. Salvia L., with ~1,000 species, makes up nearly 15% of the species diversity in the mint family and has attracted great interest from biologists across subdisciplines. Despite the great progress that has been achieved in discerning the placement of Salvia within Lamiaceae and in clarifying its infrageneric relationships through plastid, nuclear ribosomal, and nuclear single copy genes, incomplete resolution has left open major questions regarding phylogenetic relationships among and within subgenera as well as to what extent infrageneric relationships differ across genomes. We expand a previously published anchored hybrid enrichment dataset of 35 exemplars of Salvia to 179 terminals. We also reconstruct nearly complete plastomes for these samples from off-target reads. We use these data to examine concordance and discordance among nuclear loci and between the nuclear and plastid genomes in detail, elucidating both broad-scale and species-level relationships within Salvia. We find that despite widespread gene tree discordance, nuclear phylogenies reconstructed using concatenated, coalescent, and network-based approaches recover a common backbone topology. Moreover, all subgenera except for Audibertia are strongly supported as monophyletic in all analyses. The plastome genealogy is largely resolved and is congruent with the nuclear backbone. However, multiple analyses suggest that incomplete lineage sorting does not fully explain gene tree discordance. Instead, horizontal gene flow has been important in both the deep and more recent history of Salvia. Our results provide a robust species tree of Salvia across phylogenetic scales and genomes. Future comparative analyses in the genus will need to account for the impacts of hybridization/introgression and incomplete lineage sorting in topology and divergence time estimation.